2019
DOI: 10.3390/ijms20040898
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Potential of Single Metabolites of Curcuma longa Assessed in the Total Extract by Thin-Layer Chromatography-Based Bioautography and Image Analysis

Abstract: Curcuma longa from Zingiberaceae belongs to the major spices consumed around the world, known from its cholagogue, anti-inflammatory, and antimicrobial properties. Lack of data on the activity of single components of turmeric extract encouraged the authors to apply TLC (thin-layer chromatography) based bioautography studies to reveal its antimicrobial constituents and construct a universal platform for the bioactivity assessment of crude extracts, with help of a freeware ImageJ software. This optimized chromat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 25 publications
(32 reference statements)
1
10
0
1
Order By: Relevance
“…However, there was more prominent growth inhibition on the gram-positive bacteria than on the gram-negative [76]. Another study performed by Czernicka, and colleagues elucidated the antimicrobial potential of turmeric extract against several Gram-positive strains (one strain of Staphylococcus epidermidis and two strains of Bacillus subtilis), revealing that the different fractions of this extract can inhibit bacterial growth [37]. In the same way, Shakeri et.…”
Section: Antibacterialmentioning
confidence: 90%
See 1 more Smart Citation
“…However, there was more prominent growth inhibition on the gram-positive bacteria than on the gram-negative [76]. Another study performed by Czernicka, and colleagues elucidated the antimicrobial potential of turmeric extract against several Gram-positive strains (one strain of Staphylococcus epidermidis and two strains of Bacillus subtilis), revealing that the different fractions of this extract can inhibit bacterial growth [37]. In the same way, Shakeri et.…”
Section: Antibacterialmentioning
confidence: 90%
“…Turmeric's therapeutic properties may include a wide variety of conditions found in the literature, where most of them come from the bioactive compounds in its rhizome. For years different research groups have shown that turmeric is extraordinarily rich in valuables phytochemicals with pharmacological properties including polyphenols (e.g., curcuminoids), terpenes (e.g., ar-, α-and β-turmerone, α-zingiber, and β-sesquiphellandrene), flavonoids, coumarins, saponins, tannins, and steroids [36][37][38]. The principal curcuminoids are curcumin and its derivatives demethoxycurcumin and bisdemethoxycurcumin [32,39,40].…”
Section: Phytochemicalsmentioning
confidence: 99%
“…In addition to the frontier technology discussed above, broadening the application scope of TLC bioautography is, to date, the most important destination that needs to be reached. Apart from the described methods for the identification and composition screening of herbal medicines and finding new potential drugs for the treatment of serious human diseases (i.e., antibacterial components in turmeric, Ocimum sanctum and Zingiber officinale and free radical scavenger in Piper betle leaves and Salvia verticillata L.) [43,[106][107][108]. TLC bioautography has a potential in other fields, such as environmental sciences (i.e., olive processing wastewaters) [109] and agriculture (i.e., pathogens related to apple ring rot disease and multiple antibiotic residues in cow's milk) [19,34].…”
Section: Discussionmentioning
confidence: 99%
“…It has applications in a wide range of fields. Czernicka et al used mass spectrometry combined with liquid chromatography (LC-ESI-Q-TOF-MS) to research the qualitative and quantitative composition of obtained extracts, and the compounds were determined in two extracts according to the fragmentation pattern and existing scientific literature [ 43 ]. Recently, an ESI-based TLC-MS approach, named TLC-electrostatic field induced spray ionization (EFISI)-MS has been developed.…”
Section: Detection Techniquementioning
confidence: 99%
“…Furthermore, the JT - Hex extracts were rich in ar-turmerone, a -turmerone, and ß -turmerone, which are the major compounds in the essential oils of turmeric from Curcuma longa . Several studies have demonstrated that turmeric essential oils possessed potent antibacterial activity against a wide range of bacteria such as S.aureus, E.coli , P.aeruginosa , and B.subtilis [ 43 45 ]. Other phytoconstituents in JT extracts, such as squalene from Cynodon dactylon, phytol from Erythrina variegate and Azadirachta indica , and stigmasterol derived from Pongamia pinata may also contribute to the biological effects of the JT extracts.…”
Section: Discussionmentioning
confidence: 99%